Research of the information security environment of pharmaceutical organizations in the context of the transformation of pharmaceutical practice - N. O. Tkachenko; S. S. Mysiura (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The article presents the results of a study of the information security environment of the pharmaceutical sector (ISEP) amid the transformation of pharmaceutical practice in Ukraine.